2022
DOI: 10.13057/nusbiosci/n140105
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potency of n-butanol fraction of Ficus glumosa leaves against oxidative stress induced by carbon tetrachloride in the kidneys of rats

Abstract: Abstract. Abu MS, Yakubu OE, Onuche JI, Tatah SV. 2022. Antioxidant potency of n-butanol fraction on Ficus glumosa leaves against oxidative stress induced by carbon tetrachloride in the kidneys of rats. Nusantara Bioscience 14: 40-46. The kidneys play several essential roles in the body, including regulating the water and ions reabsorb from glomerular filtrate in kidney tubules. It is controlled by several hormones such as antidiuretic hormone (ADH), aldosterone, and angiotensin II. This report presented the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…Similarly, ALT also significantly decreased when group 11 (53.46 ± 4.6 U/L) was compared with group 2 (101.42 ± 16.01 U/L). This report agreed with Ugwu et al (2013); Yakubu et al, (2020) and Abu et al, (2022). The decrease in AST and ALT in the treatments groups may be attributed to the presence of flavonoids which possess a wide range of biological benefits, including organ protection, hypoglycemic, lipid-lowering, anti-oxidative, and anti-inflammatory properties (López-Lázaro, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, ALT also significantly decreased when group 11 (53.46 ± 4.6 U/L) was compared with group 2 (101.42 ± 16.01 U/L). This report agreed with Ugwu et al (2013); Yakubu et al, (2020) and Abu et al, (2022). The decrease in AST and ALT in the treatments groups may be attributed to the presence of flavonoids which possess a wide range of biological benefits, including organ protection, hypoglycemic, lipid-lowering, anti-oxidative, and anti-inflammatory properties (López-Lázaro, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…This result can be deduced that administering the evaluated polyherbal extract can ameliorate the elevated level of serum electrolytes orchestrated by paracetamol toxicity, probably due to some bioactive components such as polyphenol, glycoside, and flavonoid in the different plants. The normalization of electrolytes in this study could liken to the findings of Abu et al (2022), that used an n-butanol fraction of F. glumosa to reverse the distorted levels of sodium, chloride, and potassium ions in albino rats.…”
Section: Discussionsupporting
confidence: 62%
“…Tanko et al [52] observed that the application of n-butanol had increased the antioxidant enzymes in the Indiogfera pulchara plants. In another study, Abu et al [53] also found that the application of n-butanol had significantly increased the antioxidant potency of Ficus glumosa leaves. Chen et al [54] reported that the application of n-butanol in Ligustrum robustum induced the production of various antioxidant genes to deal with MDA and hydrogen peroxide.…”
Section: Antioxidant Enzyme Activitiesmentioning
confidence: 89%